Towards geometrical calibration of x-ray computed tomography systems—a review. (19th August 2015) - Ferrucci, Massimiliano; Leach, Richard K; Giusca, Claudiu; Carmignato, Simone; Dewulf, Wim
Abstract: Industrial x-ray computed tomography (XCT) is seen as a potentially effective tool for the industrial inspection of complex parts. In particular, XCT is an attractive solution for the measurement of internal geometries, which are inaccessible by conventional coordinate measuring systems. While the technology is available and the benefits are recognized, methods to establish the measurement assurance of XCT systems are lacking. More specifically, the assessment of measurement uncertainty and the subsequent establishment of measurement traceability is a largely unknown process. This paper is a review of research that contributes to the development of a geometrical calibration procedure for XCT systems. A brief introduction to the geometry of cone-beam tomography systems is given, after which the geometrical influence factors are outlined. Mathematical measurement models play a significant role in understanding how geometrical offsets and misalignments contribute to error in measurements; therefore, the application of mathematical models in simulating geometrical errors is discussed and the corresponding literature is presented. Then, the various methods that have been developed to measure certain geometrical errors are reviewed. The findings from this review are discussed and suggestions are provided for future work towards the development of a comprehensive and practical geometrical calibration procedure.